PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN GREEN PRODUCT SEPEDA MOTOR HONDA INJECTION DENGAN KEPUASAN SEBAGAI VARIABEL MODERASI (Survei pada Mahasiswa Fakultas Ekonomi UNISRI Surakarta) - Lamidi - -; Marjam Desma Rahadhini (Universitas Slamet Riyadi, 2013)
ABSTRACT The objectives of the research are to examine and analyses: (1) effect of product quality to customer loyalty, (2) effect of satisfaction to customer loyalty, (3) effect of the interaction between product quality and satisfaction to customer satisfaction. Population on this research are all economic faculty student’s of accounting and management majors in UNISRI Surakarta. The samples of this research consist of 100 student’s,, taken with purposive sampling. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis, the researcher uses the multiple regression analysis and moderating regression analysis, meanwhile to process the data, the SPSS Release 12 program is used. The result reveals that (1) there is a significance effect between product quality to customer loyalty at economic faculty student’s in UNISRI Surakarta. (2) there is a significance effect between satisfaction to customer loyalty at economic faculty student’s in UNISRI Surakarta. (3) Interaction of the product quality and satisfaction has significant effect on customer loyalty at economic faculty student’s in UNISRI Surakarta. Keywords: product quality, satisfaction, customer loyalty